2004
DOI: 10.1080/14763140408522835
|View full text |Cite
|
Sign up to set email alerts
|

Volleyball

Abstract: The purpose of this investigation was to detect whether differences exist concerning the dynamic and kinematic parameters of vertical squat jump (SJ) on rigid (RS) and sand (SS) surface. Fifteen elite male beach volleyball players (age: 25.6 +/- 6.2 years; height: 188.0 +/- 3.5 cm; body mass: 83.2 +/- 6.0 kg; mean +/- SD, respectively) performed SJ. Force platform and kinematic analyses were used with paired sample T-tests to evaluate the differences. Vertical jump height was significantly smaller (p < .001) o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
23
0
2

Year Published

2013
2013
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 70 publications
(28 citation statements)
references
References 28 publications
3
23
0
2
Order By: Relevance
“…Potentially, elite beach flags sprinters may allow their start to occur over a longer duration so as to generate more ground reaction force, especially against the unstable sand surface. This is similar to findings made by Giatsis et al [12] when analyzing elite beach volleyball players. When jumping on a sand surface, elite beach volleyball players will spend more time in contact with the ground, so as to generate more force and increase jump height [12].…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Potentially, elite beach flags sprinters may allow their start to occur over a longer duration so as to generate more ground reaction force, especially against the unstable sand surface. This is similar to findings made by Giatsis et al [12] when analyzing elite beach volleyball players. When jumping on a sand surface, elite beach volleyball players will spend more time in contact with the ground, so as to generate more force and increase jump height [12].…”
Section: Discussionsupporting
confidence: 92%
“…For example, the force generated during a squat jump on sand is reduced when compared to a jump on a rigid surface [12]. Giatsis et al [12] found that not only did peak force decrease, but the duration of force production was extended on sand. This is also true for maximal sprinting.…”
Section: Introductionmentioning
confidence: 99%
“…aquatic, grass or sand-based PT) could elicit similar increases in jumping and performance as traditional PT. Nevertheless, it has to be noted that performing PT on a sand surface may increase the risk of overuse injuries to the lower limbs and back (Bahr and Reeser, 2003; Giatsis and Kollias, 2004). Likewise, some studies reported no change (Brito et al, 2014; Gottlieb et al, 2014; Lehnert et al, 2013) or even slight decreases in vertical jumping performance (de Villarreal et al, 2008), probably due to the characteristics of the subject, in particular: a training level, sport activity, age, gender, familiarity with plyometric exercises and a training program (duration, volume, rest periods, frequency, type of exercises and their combination, intensity of exercises, external resistance) (de Villarreal et al, 2009).…”
Section: Discussionmentioning
confidence: 99%
“…It was shown that jumping on sand surfaces was characterized by significantly smaller jumping heights during squat jumps, countermovement jumps, volleyball spikes, and block jumps, compared with jumps on rigid surfaces [11]. Jumping height is significantly smaller on a sand surface than a rigid one due to compliance and instability of the sand, and this results in a reduction in maximum vertical forces, smaller maximum powers, vertical impulses and take-off velocity [12]. As a result of the compliance of the sand surface, during the spike jump the BVB players slow down their movements, especially during the phase of transition from knee flexion to extension and during the extension phase [13].…”
Section: Introductionmentioning
confidence: 99%